Generation of a gene-edited H9 embryonic stem cell line carrying a DOX-inducible NGN2 expression cassette in the CLYBL locus - Sara Miellet; Mitchell St Clair-Glover; Marnie Maddock; Mirella Dottori (Stem Cell Research, 2024)
The pro-neural transcription factor neurogenin-2 (NGN2) possesses the ability to rapidly and effectively transform stem cells into fully operational neurons. Here we report the successful generation of a modified H9 human embryonic H9 stem cell line containing a doxycycline (DOX) inducible NGN2 expression construct featuring a floxed Blasticidin/mApple selection module in the safe-harbor locus CLYBL. This cell line retains its pluripotent state in the absence of DOX, yet readily transitions into a neuronal state upon DOX introduction.